Gender-Based Violence: Typology and Solutions - Danilovna Shaibakova, Kamila (International Journal of Criminology and Sociology, 2022)
There are a few solutions that could at least influence the decrease of GBVAW. One of them is raising awareness, informing people about their rights and opportunities to seek help and support is crucial. Victims of GBV often experience psychological problems which come together with stigma, shame and feeling of deserving the violence. Raising awareness could be done differently, using different platforms. The social media took its stand in solving important social issues. Celebrities, influencers, micro-influencers cover the topics of GBVAW and information on how to seek help. Undoubtedly, the work of NGOs and women shelters are important as never. Thus, Educational pages, just as other pragmatic apparatuses committed to handling lewd behavior, savagery as well as sexual orientation correspondence is a need. One of the ways to raise awareness and empower women and girls is to encourage victims to speak out and seek help both legal and psychological as well as the support of the family and friends. Therefore, one of the paramount importance is to erase the shame and stigma around the GBVAW. Undoubtedly, the legal framework shall support women in their intentions to seek help. Unfortunately, this became one of the most significant problems for several countries. In numerous states, enactment tending to sex based savagery against ladies is non-existent, deficient or ineffectively actualized. As well as seeking financing to sustain the women’s shelters and hotline. That became apparent during the lockdown, a lot of the women’s support centers had to close due to the shortage of financing. COVID-19 in addition to making a lot of harm to the state of GBVAW in the world at the same time brought new ideas to fight with it. Thus, during the lockdown, some of the police forces introduced special apps for reporting a GBVAW crime. Thus, an aggressor could not understand that a report had been made. This model of reporting is an excellent tool to seek help especially when a situation is highly dangerous.